"I Had No Problems and Just Felt So Fabulous": The "Storylines" of Methamphetamine Initiation in Aotearoa/New Zealand. (July 2023) - Bax, Trent
This qualitative life course-based study analyses the key circumstances preceding methamphetamine initiation. This paper utilizes Agnew's "storylines" concept to analyse the background and situational factors that led 42 Aotearoa/New Zealanders to initiate methamphetamine. Multiple exposure to adversity across multiple life domains placed participants at heightened risk of early-onset drug use. Preceding methamphetamine initiation, the impact of social bonds and social roles were identified within the domains of family, romantic relationships, friendship and work. Whilst drug use onset broadly follows the stage theory sequence of drug use, participants did not initiate methamphetamine until age 27 on average. Initial use typically took place in a private setting among friends, family and co-workers. The initial effect was typically very positive, which greatly contributed to escalating use. Analysis revealed four main storylines, which highlight the importance of psychological state, social bonds, romantic attachments and social functioning in methamphetamine initiation.